Surgical Management of Gastroesophageal Reflux Disease: Patient Selection, Fundoplication, And Emerging Antireflux Strategies - Bryan Rodríguez Elizalde; Johan Jair Rodríguez Calderón; Marcos Rogelio Juárez Flores; Sergio Morales Acosta; Emily Villagómez Guzmán; Juan Pablo Rubén Quiroga Cruz (International Journal of Medical Science and Clinical Research Studies, 2026)
Gastroesophageal reflux disease is a chronic condition caused by failure of the antireflux barrier at the esophagogastric junction. Surgical management aims to restore this barrier by improving the function of the diaphragmatic crura, lower esophageal sphincter, and gastroesophageal flap valve. Laparoscopic Nissen fundoplication remains the reference operation for durable reflux control, although partial fundoplications and newer antireflux technologies have expanded treatment options. Antireflux surgery may provide better short-term quality of life than proton pump inhibitor therapy in selected patients, and long-term series report durable symptom control after fundoplication. However, postoperative proton pump inhibitor use, dysphagia, gas-bloat syndrome, wrap failure, and need for reoperation remain clinically relevant. The best outcomes depend on objective confirmation of reflux, appropriate symptom correlation, careful evaluation of esophageal motility, and tailored procedure selection. Partial fundoplication may reduce dysphagia and gas-bloat symptoms but can be associated with higher postoperative acid-suppression use. Magnetic sphincter augmentation and other emerging techniques may offer less disruptive alternatives in selected patients, although long-term comparative evidence continues to evolve. This review summarizes the contemporary surgical management of gastroesophageal reflux disease, emphasizing preoperative workup, operative selection, expected outcomes, complications, and special populations.